True stories about Abraham Lincoln - Gross, Ruth Belov; Turzak, Charles (New York : Lothrop, 1973)
Traces the political and personal life of the Civil War president.
Booklist
School Library Journal
4.6
K-3
Keywords: Lincoln, Abraham, -- 1809-1865 -- Juvenile literature; Lincoln, Abraham, -- 1809-1865.; Lincoln, Abraham, -- 1809-1865.; Presidents -- United States -- Biography -- Juvenile literature; Presidents; Presidents -- United States -- Biography